Sheilah McLeod: A Heroine of the Back Blocks - Boothby, Guy, 1867-1905 (Salt Lake City, UT : Project Gutenberg, 2012)
"Sheilah McLeod: A Heroine of the Back Blocks" by Guy Boothby is a novel written during the late 19th century. The story is set in Australia and centers around the lives and adventures of Jim Heggarstone and Sheilah McLeod, whose paths intertwine through various challenges, including a devastating bushfire and complex family dynamics. The book appears to explore themes of love, loyalty, and personal growth against the backdrop of the rugged Australian landscape. At the start of the narrative, we are introduced to Jim Heggarstone, who reflects on his solitary life as a white man on a South Sea island while awaiting the arrival of a trading schooner. The prologue sets up the story dramatically, showcasing Jim$1 (Bs conflicts with outsiders, notably a missionary, and foreshadowing the presence of threats to both his and Sheilah's lives. Following this, the story unfolds with Jim's recollections of his childhood, the arrival of Sheilah and her father after a flood, and their developing friendship. The opening chapters emphasize their early bond amidst the beauty and dangers of their environment, ultimately hinting at the growth of deeper feelings as they face threats together. (This is an automatically generated summary.)s
Release date is 2012-11-03
E-text prepared by D Alexander, Martin Pettit, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Australia -- Fiction; Love stories